Occupy empathy? Online politics and micro-narratives of suffering. (January 2015) - Recuber, Timothy
The Occupy movement has drawn attention to the political potential of online communities, and raised questions about the forms of emotional commitment that such communities engender. It has also generated a backlash, as supporters of the political-economic status quo have gone online to question or condemn the movement. This paper performs a discourse analysis of the messages left at one anti-Occupy site called We Are The 53%, in order to see whether such messages engaged with the idea that the current economic system creates unfair hardship and suffering. Surprisingly, the majority of the messages at We Are The 53% did not deny the existence of such hardship, but instead evinced a kind of superficial empathy with the suffering of others that viewed others' misfortune as ultimately manageable. The paper thus questions the progressive political value of empathy in online spaces.